2005
DOI: 10.1084/jem.20041378
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting frequencies of antitumor and anti-vaccine T cells in metastases of a melanoma patient vaccinated with a MAGE tumor antigen

Abstract: Melanoma patients have high frequencies of T cells directed against antigens of their tumor. The frequency of these antitumor T cells in the blood is usually well above that of the anti-vaccine T cells observed after vaccination with tumor antigens. In a patient vaccinated with a MAGE-3 antigen presented by HLA-A1, we measured the frequencies of anti-vaccine and antitumor T cells in several metastases to evaluate their respective potential contribution to tumor rejection. The frequency of anti–MAGE-3.A1 T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
169
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 215 publications
(184 citation statements)
references
References 19 publications
(29 reference statements)
13
169
1
1
Order By: Relevance
“…However, these natural pre-vaccine immune responses are often too weak to result in tumor rejection or even a reduction in tumor growth, due to the various immune suppressive mechanisms that occur within the tumor microenvironment [34]. Vaccination can then aid in boosting these spontaneous immune responses, either by aiding to overcome tumor-induced immune suppression, by re-activating anergic tumorreactive T cells at the tumor site, or by inducing new antitumor CTL clonotypes (probably due to additional antigen release from attacked tumor cells) [3,35]. This priming of the immune system by a growing tumor could explain why the immunogenicity of the mRNA sonoporated DCs was more pronounced in a therapeutic setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, these natural pre-vaccine immune responses are often too weak to result in tumor rejection or even a reduction in tumor growth, due to the various immune suppressive mechanisms that occur within the tumor microenvironment [34]. Vaccination can then aid in boosting these spontaneous immune responses, either by aiding to overcome tumor-induced immune suppression, by re-activating anergic tumorreactive T cells at the tumor site, or by inducing new antitumor CTL clonotypes (probably due to additional antigen release from attacked tumor cells) [3,35]. This priming of the immune system by a growing tumor could explain why the immunogenicity of the mRNA sonoporated DCs was more pronounced in a therapeutic setting.…”
Section: Discussionmentioning
confidence: 99%
“…The workup of the patients treated by C.W. Schmidt's group [89,90] using a laborious yet highly informative strategy [4] has shown that the vaccine-induced immune responses are dominated by highly individualized responses to shared and neoantigens generated by somatic point mutations (Thomas Wölfel, personal communication) in congruence with previous observations in select melanoma patients [3,4]. The mRNA transfection approach allows for exploring the total antigenic repertoire of tumors without limitations imposed by availability of tumor tissue, as even a few cells can provide sufficient amounts of mRNA for PCR amplification [81].…”
Section: Rna-transfection Of DCmentioning
confidence: 73%
“…Current vaccination strategies must be improved to achieve higher T-cell frequencies and most importantly, the quality of these T cells must be comparable to the protective T-cell response observed during acute or chronic viral infections. This is expected to enhance clinical efficacy, as already small numbers of highquality vaccine T cells appear to be able to induce regressions in a minority of patients by inducing a second wave of T cells (the so-called ''spark'' hypothesis) [2,3]. In addition, somatically mutated antigens, which are associated with regression and long-term survival [3,4], should be tested, as well as antigens relevant for the oncogenic phenotype (mutated and viral oncogenes, certain non-mutated antigens that tumors overexpress) to diminish antigen loss and escape [5,6].…”
Section: Why Do Cancer Vaccines Induce T Cells But So Far Exert Only mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a specific immune response does not necessarily correlate with clinical outcome. In a recent melanoma trial using a peptide specific for an epitope in MAGE-3 presented by HLA-A1, it was found that the most important response was to a completely different peptide, derived from MAGE-C2 and presented by HLA-A2 [34,35]. Furthermore, the choice of biomarker for immunological readout is often dictated by the nature of the vaccine, rather than biologically useful clinical response.…”
Section: Immunological Monitoringmentioning
confidence: 99%